Comparative efficacy of trauma scoring for predicting in-hospital mortality in elderly patients in China and Thailand: A multicenter retrospective study - Rui Lu; Ploytip Jansiriyotin; Tanyamon Kittidumkerng; Natthida Owattanapanich; Kaweesak Chittawatanarat (PLoS ONE, 2026)
Background With global population aging, trauma prediction models are essential for elderly patients, yet established scoring systems lack validation in Asian populations. This study evaluates clinical characteristics, mortality risk factors, and the predictive efficacy of trauma scoring systems in elderly trauma patients in China and Thailand. Methods This multicenter retrospective cohort study included trauma patients aged ≥65 years admitted to four Level 1 trauma centers between 01/01/2023 and 31/12/2023. The analyzed variables included demographics, clinical data, and trauma scores (ISS, NISS, RTS, TRISS, GTOS). Multivariable logistic regression and ROC curve analysis were performed. Results Among 963 patients (median age 73 years; 50.6% female), in-hospital mortality was 7.9%. Independent risk factors included age, cancer history, INR, blood transfusion, GCS, and all trauma scores. TRISS had the highest predictive value (AUC = 0.871), followed by GTOS (0.852) and RTS (0.839), all outperforming ISS and NISS. Conclusion Age, comorbidities, and trauma scores are significant predictors of in-hospital mortality in elderly trauma patients. TRISS, GTOS, and RTS offer superior prognostic performance, aiding early identification and management of high-risk individuals.